A CREATIVE IDEA OF AN UNDERGROUND TOWER CEMETERY - Oana NECULAI; Ana – Maria TOMA (Journal of Industrial Design and Engineering Graphics, 2019)
One of the biggest problems of nowadays society regarding burial sites is the lack of space and, at the same time, the huge areas that cemeteries occupy. This problem was approached during the course of “An introduction to technical creativity” and a possible solution was reached with the help of students, using brainstorming and the 3d criteria method. The proposed concept consists in building an underground cemetery, as a buried tower of minimum 20 floors down, which can accommodate hundreds of coffins. The building will appear, at the ground-floor level, like a funeral monument, but in depth, the access to the burial chambers will be made with an elevator placed at the middle of the structure. Therefore, in a world where cemeteries occupy huge areas, this concept provides an alternative to traditional customs and approaches a topic that concerns all humanity.